Handbook of antimicrobial coatings (Elsevier, 2018)
Handbook of Antimicrobial Coatings is the first comprehensive work on the developments being made in the emerging field of antimicrobial coatings. Crucial aspects associated with coating research are presented in the form of individual chapters. Particular close attention has been given to essential aspects necessary to understand the properties of novel materials. The book introduces the reader to progress being made in the field, followed by an outline of applications in different areas. Various methods and techniques of synthesis and characterization are detailed as individual chapters. Chapters provide insight into the ongoing research, current trends and technical challenges in this rapidly progressing field. The covered topics were chosen so that they can be easily understood by new scholars as well as advanced learners. No book has been written on this topic thus far with so much crucial information for materials scientists, engineers and technologists.--Provided by publisher.